Hubungan Mutu Pelayanan dengan Capaian Standar Pelayanan Minimal pada Pasien di Ruang Rawat Inap Rumah Sakit Dr. Bratanata - Bettrianto, Bettrianto; Lestari, Vina Dwi (Jurnal Riset Hesti Medan, 2023)
Minimum Service Standards for the Health Sector or Health SPM are prepared based on Government Regulation Article 4 paragraph 1 Number 65 of 2005 concerning Guidelines for the Preparation and Implementation of Minimum Service Standards (SPM). With SPM in the health sector, it is hoped that the most basic and essential health services can be fulfilled at the minimum level nationally, so as to reduce the gap in health services. Analyzing the relationship between Tangible service quality (direct evidence), Reliability (reliability), Responsivennes (responsiveness), Assurance (guarantee) and Empaty (empathy) simultaneously with the achievement of minimum service standards (SPM) for patients in the inpatient ward at Dr. Bratanata Jambi. This research is quantitative research with analytical survey methods and uses a cross-sectional design. The research was carried out by measuring independent and dependent variables at the same time. The research was carried out in the inpatient room of Dr. Bratanata Jambi. When the research was carried out in July 2021. The population of this study was all patients treated in the inpatient ward of the Dr. Bratanata Hospital, Jambi, totaling 125 people, while the sample for this study was patients treated in the inpatient ward of the Dr. Bratanata Hospital, Jambi. totaling 56 people by means of simple random sampling. There is no relationship between the quality of service Tangible (direct evidence), Reliablity (reliability), Responsivennes (responsiveness), Assurance (guarantee) and Empaty (empathy) simultaneously with the achievement of minimum service standards (SPM) for patients in the inpatient ward at Dr. . Bratanata Jambi in 2021. There is a need to improve the quality of service to hospital patients, especially regarding the service quality variables of reliability and empathy.